2020
DOI: 10.1371/journal.pntd.0008020
|View full text |Cite
|
Sign up to set email alerts
|

Pathological roles of MRP14 in anemia and splenomegaly during experimental visceral leishmaniasis

Abstract: PLOS Neglected Tropical Diseases | https://doi.funders had no role in study design, data collection and leishmaniasis caused by Leishmania major and visceral leishmaniasis caused by L. donovani, the molecule showed distinct roles in protection/pathology; although the molecule was protective against L. major infection, depletion of the molecule resulted in easing the pathology during L. donovani infection. These may prove the complexity of MRP14, but at the same time support understanding of the mechanisms behi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 53 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…Firstly, splenomegaly during experimental VL is accompanied by an increase in cell numbers [30], whilst hepatomegaly is not -as demonstrated in the present study. Secondly, our previous studies using genetically modified mice demonstrated that deficiency in host molecules BAFF and MRP14 leads to attenuation of splenomegaly, but not hepatomegaly, in L. donovani infection [30,31]. Although it is known that dysfunction or damage in the liver or the spleen often affects the other, the influence of L. donovani infection on these organs does not appear very closely connected.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, splenomegaly during experimental VL is accompanied by an increase in cell numbers [30], whilst hepatomegaly is not -as demonstrated in the present study. Secondly, our previous studies using genetically modified mice demonstrated that deficiency in host molecules BAFF and MRP14 leads to attenuation of splenomegaly, but not hepatomegaly, in L. donovani infection [30,31]. Although it is known that dysfunction or damage in the liver or the spleen often affects the other, the influence of L. donovani infection on these organs does not appear very closely connected.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we have reported that inflammatory macrophages expressing MRP8 and MRP14 accumulate in the spleen during L . donovani infection [ 28 ]. To reveal the relationship between the MRP8/14-expressing macrophages and the BAFF-producing CD11b + MN cells, the CD11b-positive or -negative fraction of the splenocytes from L .…”
Section: Resultsmentioning
confidence: 99%
“…Later, we also found an accumulation of MRP8 + mononuclear cells in the spleen of L . donovani -infected mice [ 28 ]. Because of the shared expression of MRP8/MRP14 and shared morphological characteristics in the accumulated mononuclear cells between L .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations